Pengaruh Development of Sustainability Balanced Score Card terhadap Kinerja Perusahaan dan Dampaknya pada Implementasi ESG (Environmental Social Governance) - Judijanto, Loso; Rini, Puspa; Awaludin, Dipa Teruna; Ningsih, Tri Widyastuti; Durya, Ngurah Pandji Mertha Agung (Jurnal EMT KITA, 2025)
This study was conducted to see the influence of the development of sustainability balanced scorecard on company performance and its impact on the implementation of ESG (Environmental Social Governance). This study uses a descriptive quantitative approach used in the study. The research instrument was tested using validity and reliability tests which were then processed with multiple linear regression analysis accompanied by path tests/sobelt tests in the SPSS program. The results of the analysis illustrate that the influence of BSC (Balance Scorecard) on company performance has a significant effect. The influence of BSC (Balance Scorecard) on the implementation of ESG (Environmental Social Governance) has a significant effect. The influence of company performance on the implementation of ESG (Environmental Social Governance) has a significant effect. And, the influence of BSC (Balance Score Card) on ESG (Environmental Social Governance) mediated by company performance has a significant effect.